Parameters Estimation for Modified Weibull Distribution Based on Type One Censored Samplest - Alkanani, Iden; Majeed, Dhifaf (Iraqi Journal of Science, 2024)
The three parameters distribution called modified weibull distribution (MWD) was introduced first by Sarhan and Zaindin (2009)[1]. In theis paper, we deal with interval estimation to estimate the parameters of modified weibull distribution based on singly type one censored data, using Maximum likelihood method and fisher information to obtain the estimates of the parameters for modified weibull distribution, after that applying this technique to asset of real data which taken for Leukemia disease in the hospital of central child teaching .